Transformasi Pendidikan Menuju Konservasi Berkelanjutan: Membangun Kesadaran Lingkungan dan Kepedulian Generasi Mendatang - Pravitasari, Aufa Gisti; Nugraheni, Nursiwi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The global environmental crisis is becoming increasingly urgent. From climate change and pollution to the degradation of natural resources, its impacts are increasingly being felt around the world. Given this reality, educational changes are critical to fostering awareness and concern for environmental sustainability in future generations. This article discusses the shift towards sustainable conservation in primary education in SD Lempongsari to cultivate awareness and concern for the environment in future generations. In the context of Indonesian education, where environmental problems are becoming increasingly serious, cultivating environmental awareness is very important. By cultivating a more caring environmental awareness for future generations, the educational environment of the future will shift even more towards sustainable conservation. Data shows that children’s cognitive enthusiasm for the school environment is very high.